ANALISA PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCING (NPF) MURABAHAH, DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2015-2018 - Vita Evelini Handayani Sinaga (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
Murabahah contract financing is the financing that dominates Islamic banking to date. This is the reason for the purpose of this study, namely to determine the effect of Dana Pihak Ketiga (DPK), Non Performing Financing (NPF) Murabahah, and Capital Adequacy Ratio (CAR) on Murabahah Financing. This type of research is descriptive quantitative. The object of this research is Islamic Commercial Banks with a study period of 2015-2018. The type of data used is secondary data obtained from the official website of the official website of each Islamic bank which is the object of research. The analysis method used is panel data regression analysis using Eviews software version 10. Based on the results of this study, it shows that simultaneously Dana Pihak Ketiga (DPK), Non Performing Financing (NPF) Murabahah, and Capital Adequacy Ratio (CAR) have a significant effect on Murabahah Financing. Dana Pihak ketiga (DPK) have a significant positive effect on Murabahah Financing, while Non Performing Financing (NPF) Murabahah, have no significant negative effect on Murabahah Financing and Capital Adequacy Ratio (CAR) have no significant positive effect on Murabahah Financing.